Simultaneous Compression and Cooling in Vapor Compression Refrigeration System (International Journal of Current Engineering and Technology, 2014)
Vapor compression refrigeration systems are employed in almost all commercial, industrial and home refrigeration and HVAC systems. The compressor work represents a major part of the total energy consumption of this system. This compressor work is increased substantially by the heating of refrigerant gas during compression. This paper suggests a modification to reduce the work input to compressor thereby increasing the efficiency and Coefficient of Performance (COP) of the system. The modification consists of simultaneous cooling and compression of refrigerant to reduce pressure of gas and thus work rate required of compressor.
Keywords: Vapor Compression Refrigeration; Heat exchanger; compressor; COP; Simultaneous Compression and Cooling